TANGGUNG JAWAB DIREKSI TERHADAP PARA INVESTOR DALAM MENJALANKAN PERSEROAN (Ditinjau Dari Undang-Undang Perseroan Terbatas) - hisar siregar (Magister Hukum Universitas HKBP Nommensen, 2022)
A Limited Liability Company is a form of legal entity in the economic field in Indonesia and is one of the pillars of national economic development. The capital structure in a company business entity consists of shares owned by people or parties with the same interests. As a business entity in the form of a legal entity, of course it has an interest as it exists in humans. The position of a limited liability company is a legal subject whose position, rights and obligations are the same as humans before the law, so that in carrying out its activities and activities, of course there are company organs that run it. the directors are one of the parties responsible for managing the company in accordance with the goals of the company. This is because the directors are trustees as well as agents for limited liability companies. It is said to be a trustee, because the directors manage the company's assets, and are said to be agents, because the directors act out for and on behalf of the company. Research conducted using normative research types and can also be called doctrinal legal research. Normative law research serves to provide juridical arguments when there is a vacuum, ambiguity, and conflict of norms. In general, the approach in normative legal research consists of: statutory approach, conceptual approach, legal history approach, comparative approach and case approach. In running the company, if the directors carry out their responsibilities in accordance with applicable regulations and also in good faith and the precautionary principle, then the losses suffered by the company are not the responsibility of the company's directors. However, if the company's losses arise from within the directors themselves, such as being negligent in carrying out their responsibilities, then the losses suffered by the company can ensnare the directors to their personal assets.